Saberes docentes sobre figuras geométricas planas: contribuições do FIPLAN no ensino e na aprendizagem na educação infantil. - Moreira, Tauane Gomes (2019)
The present research deals with the teaching knowledge of a teacher of the municipal public network of Fortaleza regarding the teaching and learning of flat geometric figures in Early Childhood Education. The general objective of the research was to analyze the teachers' knowledge reelaborated by a teacher of a group of Infantile V from the use of the Fiplan. The specific objectives were: (1) To characterize the articulation of the teaching knowledge of a teacher of a group of Infantile V on flat geometric figures; (2) To identify the contributions of the didactic resource Fiplan in relation to the teaching knowledge of a teacher of a group of Infantile V on flat geometric figures; (3) To evaluate with a teacher of a group of Infantile V the implementation of proposals of pedagogical performance referring to the flat geometric figures from the use of the Fiplan. The Fiplan is a set of 60 (sixty) pieces of flat geometric figures, which are differentiated by 3 (three) attributes: format, color and size. This qualitative research was carried out in 3 (three) phases: i) observation, ii) interview, iii) continuous training with programming, as well as planning, implementation and evaluation of activities. Initially, situations occurred that, even without involving the content on flat geometric figures, the teacher could have opportunized the expansion of the children's knowledge. In the interview, some conceptual and methodological conflicts were identified. In the last phase, the teacher began to include the geometric content in their activities, proposing to the children new experiences and adapting the use of materials that respected the characteristics of the flat geometric figures and favoring the construction of the students' thinking. We conclude that the teacher reduced her conceptual gaps in the teaching of flat geometrical figures, planning situations in favor of children 's elaboration of concepts and not just the identification and naming of flat geometric figures. In relation to existential knowledge, she had the flexibility and commitment to transform her gaze on the teaching and learning of flat geometric figures. These changes in teacher knowledge were expressed in the pedagogical practices developed during the research.